ANALISIS KEMAMPUAN PENALARAN MATEMATIS DI TINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP NEGERI 3 SUNGAI RAYA - Oktaviani, Nila (Universitas Tanjungpura, 2026)
This study aims to describe students' mathematical reasoning abilities in terms of their learning styles in Grade VIII. This research is a qualitative study with a descriptive approach. The instruments used in this study are a learning style questionnaire, a mathematical reasoning test, and interview guidelines. The subjects of this study consisted of 9 students selected from class VIII G at SMP Negeri 3 Sungai Raya. Based on the learning style questionnaire, 3 students with a dominant visual learning style, 3 with a dominant auditory learning style, and 3 with a dominant kinesthetic learning style were selected. The results of the study show that students with a dominant visual learning style tend to be better at making conjectures and performing mathematical manipulations. However, students with a dominant auditory learning style demonstrated the ability to provide logical reasoning for a given problem, while students with a dominant kinesthetic learning style were able to both make conjectures and provide logical reasoning. The conclusion of this study is that there are differences in the characteristics of mathematical reasoning abilities based on students' dominant learning styles. Therefore, teachers need to consider learning styles when designing effective learning strategies.